Religiositas dan Penyesuaian Psikologis Ibu Rumah Tangga Selama Pandemi COVID-19 - Raudatussalamah - Raudatussalamah; Afifah Ismi'raj; Mukhlis Mukhlis (LPPM Universitas Abdurrab, 2024)
The covid 19 pandemic has a great influence on the psychological condition of individuals, especially housewives. So that good psychological adjustment is needed. The study aims to determine the relationship between religiosity and psychological adjustment in housewives during the COVID-19 pandemic. Sampling was carried out using purposive sampling techniques with subjects as many as 385 housewives in Limapuluh Kota district. Data collection using 2 research instruments, namely the scale of religiosity from Fetzer and the scale of psychological adjustment compiled by referring to De Vito's theory. The results showed that there was a relationship between religiosity and psychological adjustment in housewives with a correlation coefficient value of 0.318 with a significance level of p< 0.001 with a contribution to psychological adjustment of 10.1%. Psychological adjustment in housewives can be improved through religiosity.